Pengaruh Penggunaan Metode Snowball Throwing Terhadap Keaktifan Belajar Siswa Pada Pembelajaran PAI di SMP N 3 Bukittinggi - Ade Safira; Arifmiboy Arifmiboy; Darul Ilmi; Yelfi Dewi (Pusat Riset dan Inovasi Nasional, 2023)
The problem in this research is motivated by the results of the author's initial observations at SMP N 3 Bukittinggi, where the lack of enthusiasm of students in learning Islamic Religious Education, the methods used by teachers are still conventional, do not attract the attention of students and lack of interaction between teachers and students so that students students become less active, less focused, sleepy and lazy. The aim of this research was to determine the significant effect of the snowball throwing method on student learning activity. This type of research is an experiment with class VII.2 as an experiment that is treated using the snowball throwing method and VII.3 as a control class that is not given treatment. This research is a type of experimental research, with a static group comparison design. To obtain data using a questionnaire instrument. the data analysis technique uses the instrument test first, namely; validity test, reliability test. To test the prerequisites using normality and homogeneity tests and hypothesis testing is carried out, namely the t test to find out whether the hypothesis is rejected or accepted. Before testing the hypothesis, the instrument was tested first to find out valid and reliable data. After testing the instrument, then testing the hypothesis with the T-Test test to find out if the hypothesis is rejected or accepted, so that it can be seen whether the snowball throwing method has an effect on student learning activity. The results of this study indicate that based on the calculation of the activeness questionnaire t-test, the sig. (2-tailed) = 0.000 <0.05 at a significance level of 5% so that Ho is rejected and Ha is accepted. So it is proven that there is a significant influence of the snowball throwing learning method on student learning activeness in PAI learning at SMP N 3 Bukittinggi.